2020
DOI: 10.1049/iet-epa.2019.0805
|View full text |Cite
|
Sign up to set email alerts
|

Study of suppression of vibration and noise of PMSM for electric vehicles

Abstract: Zeroth‐order spatial electromagnetic force wave has been regarded as one of the main sources for electromagnetic vibration and noise of integer slot multipole permanent magnet synchronous machine (PMSM) used in electric vehicles. In this study, the 48‐slot‐8‐pole built‐in permanent magnet synchronous motor for a vehicle was taken as an example. The main sources and characteristic parameters (frequency and amplitude) of the zeroth‐order force wave of the integer slot multipole PMSM were presented. Based on this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
(31 reference statements)
0
21
0
1
Order By: Relevance
“…PMSMs, on account of their high efficiency and high power density, are becoming increasingly important in the sectors of manufacturing and transportation. New problems have appeared, such as the electromagnetic noise and vibration in PMSMs [ 1 , 2 , 3 , 4 ]. The noise signature of PMSMs deserves further attention and research in order to improve the comfort of human hearing.…”
Section: Introductionmentioning
confidence: 99%
“…PMSMs, on account of their high efficiency and high power density, are becoming increasingly important in the sectors of manufacturing and transportation. New problems have appeared, such as the electromagnetic noise and vibration in PMSMs [ 1 , 2 , 3 , 4 ]. The noise signature of PMSMs deserves further attention and research in order to improve the comfort of human hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent magnet synchronous motor (PMSM) [1][2][3] is widely used by virtue of its high efficiency and high power density. PMSM is divided into interior permanent magnet synchronous motor (IPMSM) and surface permanent magnet synchronous motor (SPMSM) according to the different installation positions of permanent magnets of the motor.…”
Section: Introductionmentioning
confidence: 99%
“…The total sound pressure level (SPL) under the rated working condition of PMM is reduced by 2.71 dB . 21 Xiaohua Li et al (2020) studied the 8pole and 48-slot embedded PMM with rated power of 5 kW, and the vibration and noise parameters of PMM were reduced by optimizing the rotor chamfer. Maximum vibration acceleration was decreased by 8.42% .…”
Section: Introductionmentioning
confidence: 99%
“…Maximum vibration acceleration was decreased by 8.42% . 22 In a comprehensive study of stator modal, Xiaoyuan Wang et al (2019) reported that when the aspect ratio of the stator is less than 0.3, the error of modal parameters calculated by the analytical method is larger. When the aspect ratio is in the range of 0.4-1, the error is less than 10% .…”
Section: Introductionmentioning
confidence: 99%